Relevansi Pendekatan Semantik Pada Lirik Lagu “Bertaut” Karya Nadin Amizah Dengan Pembelajaran Teks Puisi - Elsa Novianti (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Literary works in the form of songs are a form of literary work that has lyrics or can be said to be poetry. When learning Indonesian, students do not understand the similarities between songs and poetry. This research aims to determine the semantic meaning of songs which are related to the physical structure of poetry and can be understood in learning Indonesian in poetry texts. The method used in the research is descriptive qualitative method. The techniques used in this research are note-taking and research techniques. The aim of this technique is to achieve a deep understanding of the meaning of the song